Seeing What's Possible: Videos are more Effective than Written Portrayals for Enhancing the Relatability of Scientists and Promoting Black Female Students' Interest in STEM. - Pietri, Evava S.; Johnson, India R.; Majid, Sana; Chu, Charles (Sex Roles, 2021)
Although interactions with Black female scientists can alter beliefs about STEM (science, technology, engineering, mathematics) and encourage Black female students' interest in these fields, this strategy may overburden the few Black women working in STEM. To address this issue, we explored whether a brief video presentation of a Black female computer scientist would be an effective intervention compared to an identical written transcript. We found that participants from the general U.S. population (Experiments 1, n = 201, and 2, n = 745) and Black women U.S. students (Experiment 3, n = 217) perceived the computer scientist as warmer and felt more virtual connection (i.e., sense of friendship, identification) with the scientist in video compared to written format. The video also was more effective for promoting feelings of friendship with the scientist relative to audio alone or a written transcript with pictures (Experiment 2). Most importantly, Black female students who watched the video of the computer scientist reported greater interest in computer science compared to those who read about the computer scientist and those in a no narrative control condition (Experiment 3). The current findings not only demonstrate that videos are useful tools for diversity practitioners but also highlight the importance of representation in popular movies and TV shows.